Dementia worry in middle-aged and older adults in Germany: sociodemographic, health-related and psychological correlates - Bowen, Catherine E.; Kessler, Eva-Marie; Segler, Julia (European journal of ageing, 2019)
“Dementia worry” (DW; i.e., concern about developing dementia) is highly prevalent in the general population. However, research on the characteristics associated with lower and higher levels of DW is still limited. Based on previous empirical and conceptual work, we examined the extent to which DW was related to a comprehensive range of objective and subjective characteristics (sociodemographics, contact with people with dementia, physical health-related risk factors, well-being/psychological distress, aging self-perceptions, social-cognitive health beliefs about dementia). A convenience sample of N = 219 German adults 40 + years (M = 65.50 years, SD = 11.34; 40-94 years) reporting no dementia or cognitive impairment diagnosis completed questionnaires. We improved upon previous research by using a ten-item scale to measure DW. We used bivariate correlations and multivariate regression to examine the extent to which DW was related to the potential concomitants. 41.1% of the participants indicated DW. Together, the predictor variables explained 53.3% of the variance in DW. DW was related to psychological distress, perceived memory change, aging anxiety, and personal risk perception in both the bivariate and multivariate analyses. There was a quadratic (reverse U shape) relationship between age and DW. Physical health-related risk factors were not related to DW. Our findings suggest that DW represents a hybrid of psychological distress, aging self-perceptions, and a specific type of health concern. Healthcare practitioners should consider a person’s psychological characteristics when deciding how to intervene when someone indicates moderate or high DW.
First Online: 28 February 2018
Gesehen am 31.05.2019